Manejo biológico e químico no controle de percevejo-marrom da soja - Soares, Franciéle dos Santos (2023)
The brown stink bug Euschistus heros (F.) is currently the most important species of hemiptera that occurs in soybeans, presenting control difficulties by chemical insecticides, compared to the other stink bugs. The present work presents two chapters that aim to analyze the effectiveness of entomopathogenic fungi, how contamination occurs, what are the modes of transfer and entry, on the mortality of E. heros and the integration of microbiological insecticides and chemical insecticides in the control of nymphs and adults of E. heros in the soybean crop. The first entitled “Efficacy of the entomopathogenic fungi Beauveria bassiana and Metarhizium anisopliae in the control of E. heros adults, via the application of different modes of transfer and entry”, which evaluates the effect and effectiveness of entomopathogenic fungi and microbiological insecticides on adults of E. heros. Bioassays were conducted under controlled conditions, using B. bassiana and M. anisopliae, by four possible routes: topical contact, tarsal contact, ingestion and immersion contact. The bioassay was conducted under a completely randomized design regiment, with 10 replications and five insects per replication. The results allow us to conclude that Bometil® (B. bassiana, IBCB 66 - 4.3 x 108 conidia/g + M. anisopliae, IBCB 425 - 3.2 x 108 conidia/g) is more effective in terms of mortality and has a shorter lethal time for both transfer and input modes. In the second chapter, entitled “Integration of chemical and biological methods in the management of nymphs and adults of E. heros”, the objective was to quantify the effectiveness of isolated microbiological insecticides and those associated with chemical insecticides applied to soybeans. In experiment 1, seven treatments were evaluated, three isolated from entomopathogenic fungi (EPF), three commercial microbiological products and one control. In experiment 2, the treatments consisted of a control, three chemical insecticides, three EPF isolates, three commercial microbiological products and combinations between chemical and microbiological treatments, totaling 16 treatments. The results allow us to conclude that the efficacy of isolates of entomopathogenic fungi and microbiological insecticides varied for nymphs between 22% and 94%, and for adults between 16% and 75%, while the efficacy of the the association of microbiological and chemical insecticides varied for nymphs between 34% and 98%, and from adults between 22% and 98%. It is concluded that the entomopathogenic fungi both isolated and associated with chemicals insecticides are efficient to cause mortality of E. heros in laboratory bioassays and under field conditions.